2018
DOI: 10.1007/s10903-018-0735-4
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Mobility and Goal-Striving Stress Among Black Americans: The Roles of Ethnicity and Nativity Status

Abstract: Goal-striving stress refers to the psychological consequences of seeking but failing to reach upward mobility and is more common among low-income and people of color. Intergenerational mobility-or improved socioeconomic standing relative to one's parents-may be an important predictor of goal-striving stress for Blacks. We used the National Survey of American Life to investigate the association between intergenerational mobility and goal-striving stress among U.S.-born African Americans, U.S.-born Caribbean Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…As far as we could tell, only one recent study has examined predictors of aspiration strain (Mouzon et al. ), but even this study neglected to consider the role of religion. A slew of empirical findings has already confirmed that religiously involved people tend to report greater optimism and life satisfaction over their life course (e.g., Krause ; Lim and Putnam ), which has clear implications for religion's role in diminishing aspiration strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we could tell, only one recent study has examined predictors of aspiration strain (Mouzon et al. ), but even this study neglected to consider the role of religion. A slew of empirical findings has already confirmed that religiously involved people tend to report greater optimism and life satisfaction over their life course (e.g., Krause ; Lim and Putnam ), which has clear implications for religion's role in diminishing aspiration strain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the research avenues sketched above, future inquiries could advance our knowledge of aspiration strain by exploring whether dimensions of religious involvement, aside from buffering the adverse effects of high levels of aspiration strain, also help to reduce aspiration strain from the outset. As far as we could tell, only one recent study has examined predictors of aspiration strain (Mouzon et al 2018), but even this study neglected to consider the role of religion. A slew of empirical findings has already confirmed that religiously involved people tend to report greater optimism and life satisfaction over their life course (e.g., Krause 2005;Lim and Putnam 2010), which has clear implications for religion's role in diminishing aspiration strain.…”
Section: Discussionmentioning
confidence: 99%
“…First, to speak directly to the debate in the literature and to minimize confounding from competing factors, we followed prior research (Goldthorpe 1983;Sobel et al 2004) and used a selected group of US-born men in the mobility-fertility analysis. To be sure, the experience of and/or the response to social mobility are likely different depending on individuals' social and demographic characteristics, so we do not assume that social mobility uniformly affects individuals' well-being (Akee et al 2019;Breen and Whelan 1995;Cheng 2020;Cheng et al 2019;Friedman 2014;Goldscheider and Uhlenberg 1969;Mouzon et al 2018;Vallejo 2012). For example, women may be more susceptible to negative mobility effects because that women are more likely to be affected by interpersonal and social stressors (Matud 2004;Rudolph 2002).…”
Section: Discussionmentioning
confidence: 99%
“…First, to speak directly to the debate in the literature and to minimize confounding from competing factors, we followed prior research (Goldthorpe 1983;Sobel et al 2004) to use a selected group of US-born men in the mobility-fertility analysis. To be sure, the experience of and/or the response to social mobility are likely differ depending on individuals' social and demographic characteristics, so we do not assume that social mobility uniformly affects individuals' well-being (Akee et al 2019;Breen and Whelan 1995;Cheng 2020;Cheng et al 2019;Friedman 2014;Mouzon et al 2018). For example, women may be more susceptible to negative mobility effects on the basis that women are more likely to be affected by interpersonal and social stressors (Matud 2004;Rudolph 2002).…”
Section: Discussionmentioning
confidence: 99%